Pengaruh Social Support terhadap Loneliness pada Mahasiswa Rantau di Kota Bandung - Kezkia Meianisa; Sita Rositawati (UNISBA Press, 2023)
Abstract. The results of research on social support show that social support has many benefits in overcoming various problems. One of the benefits of social support is to help overcome loneliness, where loneliness according to Russell (1996) is